2021
DOI: 10.1093/ofid/ofab042
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Symptoms in Patients Recovering From COVID-19 in Denmark

Abstract: Background Although persistent symptoms after Coronavirus disease 2019 (COVID-19) are emerging as a major complication to the infection, data on the diversity and duration of symptoms are needed. Methods Patients aged ≥18 years with a positive polymerase chain reaction (PCR) test for severe acute respiratory syndrome coronavirus 2 and hospitalized at the Department of Infectious Diseases, Aarhus University Hospital, Denmark, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 33 publications
6
82
0
1
Order By: Relevance
“…Numerous research groups reported widespread persisting symptoms in COVID-19 patients for up to 6 months after SARS-CoV-2 infection (70,75,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous research groups reported widespread persisting symptoms in COVID-19 patients for up to 6 months after SARS-CoV-2 infection (70,75,(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
“…They also described practice on the management of post-acute COVID-19 and performed comprehensive analyses of health-related quality of life (70,75,123). Furthermore, numerous editorials, reviews, news articles, clinical updates, narrative interviews, and focus groups have been published to explore what it is like to live with long-term COVID-19, also trying to emphasize the putative pathophysiology, risk factors, and treatments (124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142). Two cohort studies on severe/critical COVID-19 patients reported persistent physiological impairment and decrease in quality of life in more than half of the patients at up to 6 months of follow up (77,100).…”
Section: Widespread Persistent Symptomsmentioning
confidence: 99%
“…Some authors referred to ‘long COVID-19 syndrome’ [ 2 , 4 , 5 , 6 ], ‘post-COVID-19 syndrome’ [ 7 , 8 ], or ‘post-acute COVID-19 syndrome’ [ 3 , 9 ], a syndrome that can possibly have an impact on the quality of life of patients [ 10 ]. The most common persistent symptoms in COVID-19 are fatigue and breathlessness [ 8 , 11 , 12 ]. Neurological symptoms, such as headaches [ 4 , 5 , 8 , 11 , 12 ]; otorhinolaryngological symptoms [ 11 , 13 ], such as olfactory and gustatory dysfunctions; psychiatric symptoms, such as concentration problems, sleep difficulties, and anxiety [ 11 , 14 ] are also common long-term consequences of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The most common persistent symptoms in COVID-19 are fatigue and breathlessness [ 8 , 11 , 12 ]. Neurological symptoms, such as headaches [ 4 , 5 , 8 , 11 , 12 ]; otorhinolaryngological symptoms [ 11 , 13 ], such as olfactory and gustatory dysfunctions; psychiatric symptoms, such as concentration problems, sleep difficulties, and anxiety [ 11 , 14 ] are also common long-term consequences of COVID-19. Although considerable progress has been made in treating COVID-19, very little is known about the long-term consequences of this infection.…”
Section: Introductionmentioning
confidence: 99%
“…( 63 , 64 , 65 ). The most frequent reported symptoms include cognitive impairment, dyspnea, loss of smell and taste, and mental and physical fatigue ( 9 , 10 , 11 , 66 ). Life quality are affected, and patients suffering from LTC experience problems performing daily activities and work ( 67 ).…”
Section: Patients With Post Infectious Long-term Covid-19 Sequelaementioning
confidence: 99%